IMPLEMENTASI STRATEGI KOMUNIKASI ORGANISASI UNTUK MENINGKATKAN KENYAMANAN LINGKUNGAN KERJA - Sry Ayu Pitaloka Saragih; Michael Jibrael Rorong (SCIENTIA JOURNAL, 2026)
Workplace comfort is an important factor in supporting organizational sustainability and effectiveness. In addition to physical conditions, workplace comfort is strongly influenced by the quality of communication developed within the organization. Strategically managed organizational communication plays a crucial role in creating psychological safety, role clarity, and harmonious working relationships between leaders and employees. Therefore, this study aims to examine the implementation of organizational communication strategies in enhancing workplace comfort.This study employs a qualitative descriptive approach. Data were collected through in-depth interviews, observation, and document analysis related to internal communication practices within the organization. Informants were selected purposively, consisting of management and employees who are directly involved in organizational communication processes. Data were analyzed using thematic analysis to identify patterns, themes, and meanings related to organizational communication strategies and workplace comfort.The findings indicate that the implementation of organizational communication strategies emphasizing information openness, two-way dialogue, and appropriate internal communication channels contributes to the creation of a comfortable work environment. Transparent and dialogic communication enables employees to feel valued, involved, and clear about their roles. Furthermore, a communication culture characterized by mutual respect and empathy plays a significant role in fostering a positive and psychologically safe workplace climate.This study concludes that organizational communication strategies function not only as tools for information dissemination but also as mechanisms for constructing meaning and work relationships that support workplace comfort. The findings are expected to contribute theoretically to the field of organizational communication and provide practical insights for organizations in designing and implementing communication strategies oriented toward employee comfort and well-being.